On Modulated NLS-Ermakov Systems. (21st December 2017) - Rogers, Colin; Chow, Kwok
Abstract : Spatial modulated coupled nonlinear Schrödinger systems with symmetry reduction to integrable Ermakov and Ermakov-Painlevé subsystems are investigated.